Epistemological conceptions about enviromental culture and civilization project - Columbie Puig, Novalis (M+A. Revista Electrónica de Medioambiente, 2013)
In a century in which the economic, scientific-technical, cultural, political, require a better knowledge of the surrounding reality becomes necessary environmental culture that promotes increased opportunities for reflection and action.Precisely this guideline aims to this study. The environmental culture as a foundation that responds to emergencies of our time. The research is based on theoretical research methods: historical-logical, analytic-synthetic, inductive-deductive, among others. Research shows that the cultural peculiarities of men, their habits, customs, behavior patterns and value systems must meet fund to facilitate awareness to existing environmental problems, which should become a constant concern all, this is the only solution to the holocaust humanity living today.
Keywords: culture; environmental awareness; environmental education.